Catalytic Performance Enhancement Of Nickel Doped Calcium Oxide For Biodiesel Production - Phang, Kai Sheng (2020)
The demand of energy is growing continuously with the increase in population around the world annually. The development of clean and renewable energy sources has become important owing to rapid surge in crude oil price, diminishing fossil fuel reserves and increasing environmental pollution due to fuel burning from petroleum-fueled engines. In this context, biodiesel is emerged as a renewable and eco-friendly alternative to the conventional diesel fuel as it is non-toxic and biodegradable. However, in the current state of energy crisis urgency, the biodiesel has yet to replace the fossil-based diesel fuel effectively as the primary energy source ascribed to the high cost which is contributed significantly from the synthesis of catalyst used in biodiesel production. In this regard, waste eggshells are chosen as the raw materials to derive a cost-effective and environmental-friendly catalyst in reducing the overall biodiesel production cost. The catalytic activity of waste eggshellsderived CaO catalyst is improved by synthesising it in nanocrystalline form, while the metal dopants are impregnated to CaO catalyst in order to further enhance its catalytic performance as the rate of transesterification catalysed by neat CaO is still inadequate for practical application. In this research, the active doped CaO nanocatalyst is synthesised by the calcination of waste eggshells at 900 ℃ under air flow before being wet impregnated with nickel dopants at the amount varying from 1 wt% to 5 wt%, followed by re-calcination at the temperature varying from 600 ℃ to 900 ℃. The physicochemical properties of synthesised catalysts are analysed using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy, temperature-programmed desorption of carbon dioxide (CO2-TPD) and thermogravimetric analysis (TGA). The analysis results reveal that the doping process is capable of enhancing the properties of CaO catalyst such as particle size, surface area and basicity. From XRD analysis, the crystallite size of CaO catalyst is reduced from 59.62 nm to a minimum of 41.25 nm after the impregnation of Ni dopant. SEM analysis reveals that the doping process transforms the morphology of catalyst from uniform (coral) shape into irregular shape along with the increment in surface porosity and reduction in particle size, signifying an increased surface area. Based on CO2-TPD analysis, the vi impregnation of Ni dopant is able to enhance the basicity of CaO catalyst, where it shows an increment from 1599.53